Bretton Woods revisited : evaluations of the International Monetary Fund and the International Bank for Reconstruction and Development - Acheson, A. L. Keith; Chant, J. F.; Prachowny, Martin F. J.; World Bank. (London : Macmillan, 1972)
This is the proceedings of the conference on 2nd and 3rd June 1969 held at Queen's University to commemorate the twenty-fifth anniversary of the Bretton Woods Agreements.
Papers delivered at a conference at Queen's University, Kingston, Canada on 2nd and 3rd June 1969.
Includes bibliographical references.
rua 19/06/17
Loans
Keywords: International finance; International Monetary Fund